Key factors influencing the competitiveness of Indonesian halal product exports: A prospective analysis with MICMAC approach - Aini, Nur; Go, Riska Tezara (Journal of Halal Science and Research, 2026)
Although Indonesia is the country with the largest Muslim population in the world and has great potential in the global halal industry, the competitiveness of Indonesian halal product exports still lags behind countries such as Malaysia and the United Arab Emirates. This study aims to identify the key factors that influence the competitiveness of Indonesian halal product exports and to develop strategic recommendations to strengthen its position in the global market. The study employs a prospective analytical approach using qualitative descriptive methods based on literature reviews, secondary data analysis, and stakeholder mapping through the MICMAC matrix. The findings reveal that variables such as institutional capacity, halal auditor quality, regulations, and inter-institutional collaboration are the primary drivers of the system, while factors like market demand and product innovation are significantly influenced by these conditions. In conclusion, institutional strengthening, standard harmonization, and collaborative strategies are key to enhancing competitiveness. Implications include the need for integrated cross-sectoral policies and long-term investment in the Halal Product Assurance ecosystem. Keywords: Halal culinary area, Halal value chain, Islamic business model, Local economic development, MSME business incubation.